2021
DOI: 10.34172/ijhpm.2021.79
|View full text |Cite
|
Sign up to set email alerts
|

Length of Stay, Hospital Costs and Mortality Associated With Comorbidity According to the Charlson Comorbidity Index in Immobile Patients After Ischemic Stroke in China: A National Study

Abstract: Background: In this study, we examined the length of stay (LoS)-predictive comorbidities, hospital costs-predictive comorbidities, and mortality-predictive comorbidities in immobile ischemic stroke (IS) patients; second, we used the Charlson Comorbidity Index (CCI) to assess the association between comorbidity and the LoS and hospitalization costs of stroke; third, we assessed the magnitude of excess IS mortality related to comorbidities. Methods: Between November 2015 and July 2017, 5114 patients hospitalized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 56 publications
1
7
0
Order By: Relevance
“…The following outcomes were measured: death (record all-cause mortality within 90 days, which consists of in-hospital deaths), LoS (duration of hospitalization) ( 38 ), and nonelective readmission (second and subsequent hospitalizations during the period analyzed) during the 90 days following discharge.…”
Section: Methodsmentioning
confidence: 99%
“…The following outcomes were measured: death (record all-cause mortality within 90 days, which consists of in-hospital deaths), LoS (duration of hospitalization) ( 38 ), and nonelective readmission (second and subsequent hospitalizations during the period analyzed) during the 90 days following discharge.…”
Section: Methodsmentioning
confidence: 99%
“…Unfavorable disease course has been especially associated with chronic metabolic comorbidities, such as arterial hypertension, diabetes mellitus, hyperlipoproteinemia, and obesity ( 2 - 7 ). Charlson comorbidity index (CCI), a summary measure of comorbidities validated as a prognostic tool in a number of chronic and malignant diseases ( 8 , 9 ), has also been associated with an adverse COVID-19 clinical course ( 10 - 15 ).…”
mentioning
confidence: 99%
“…Also, Tornes et al showed that dementia in uences the patient's acute hospital length of stay 29 . According to Liu et al, dementia was the most notable length of stay-speci c and cost-speci c comorbidities among patients after stroke 30 .…”
Section: Discussionmentioning
confidence: 99%